Application of push & pull theory in Island sport tourism: a study of Sipadan Island, Sabah - Dolinting, Erica E.; Yusof, Aminuddin; Chee, Chen Soon (University of Pitesti, Romania, 2015)
The purpose of this paper is to further the understanding of island sport tourism in Sabah, Malaysia. Specifically, the authors utilised the push and pull theory to examine how motives and destination image attract sport tourists to spend their holidays in Sipadan Island, Sabah, Malaysia. Findings indicate that domestic sport tourists were more significantly motivated by intellectual, social, stimulus-avoidance and competence mastery motives than international sport tourists. With respect to the pull factors, result shows some difference in perceptions of destination image between domestic and international sport tourists. The findings of the study suggest that: (1) market segmentation based on demographic profiles can be identified, (2) four push motives should be emphasized on promotional efforts and (3) unique packages of sport tourism experiences should be developed in regards to sport tourism in Sipadan Island, Malaysia.